UJI SIRIH MERAH (Piper crocatum Ruiz and Pav. ) PADA BERBAGAI INTENSITAS SINAR MATAHARI DAN MEDIA TANAM - -, Sumarwoto; -, Susilowati; Adhityanti, Yanning (MAPETA, 2008)
The aim of this research was to determine the test of Sirih Merah on sunlight intensity and planting medium. The experiment was conducted in paranet house at the Faculty of Agriculture UPN "Veteran" Yogyakarta (± 105 m above sea level), from September to December 2006. The experimental was designed using Split Plot Design with two treatments factors and three replications. The mainplot is various of sunlight intensities: I1= intensity 25%, I2= intensity 50%, I3 = intensity 75%, I4 = intensity 100%. The sub-plot was planting medium ( M): M1 = 1: 1:1 (Chaff charcoal : Sand : Compost), M2 = 1: 1: 1 ( Sphagnum moss : Sand : Compost), and M3 (Bamboo Mulch : Sand : Compost).The results showed that there was an interaction between type of medium and sunlight intensity that resulted in significantly longer of leaf bud, number of leaves, and wide of leaf. Treatment with light intensity I1 ( 25%) resulted in the longest leaf, the best quality of leaf (leaf colour, chlorophyll and of tannin content), the highest fresh plant weight, and the biggest root volume better than other higher light intensities. The growth and the quality of Sirih Merah was not affected by planting medium, however chaff charcoal might be a better option to use, because it is cheaper and easier to obtain.Keywords : Sirih Merah (Piper crocatum Ruiz and Pav.), light intensity, planting medium